Music and its Narrative Potential (Brill, 2024)
“Music and its Narrative Potential” is a book about musical stories. It is a collection of thoughts on how music evokes narratives through its own medium-specific strategies. This book is a versatile consideration of narratives expressed through music. There are several threads that flow and recur through its different chapters, namely contemporary music, interdisciplinary approaches, contemporary narratology, or intermediality.